The Impact of Risk Management Practices on Bank Performance: A Systematic Literature Review - Rony Susalit; Agus Rahayu; Disman Disman; Mayasari Mayasari (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The banking sector plays a crucial role in driving economic growth and maintaining financial stability by directing funds to productive sectors while managing risks that affect profitability and resilience. This study uses a Systematic Literature Review (SLR) guided by PRISMA principles to explore how risk management practices, especially Non-Performing Loan (NPL) management, influence bank performance. Lending, as the core banking activity, is key to profitability and financial intermediation, yet high NPL levels can undermine income and stability, particularly in developing countries like Indonesia. By reviewing 16 recent empirical studies, the findings show that effective risk management including strong credit governance, adherence to Basel III standards, technology-supported lending systems, and an empowered Chief Risk Officer helps reduce NPLs and improve financial performance as reflected in ROA, ROE, NIM, and other risk-adjusted indicators. Furthermore, a comprehensive approach that combines regulatory compliance, risk diversification, and sustainability strengthens long-term resilience. These insights provide practical guidance for regulators, bank managers, and researchers in designing flexible, transparent, and sustainable risk management strategies. The study emphasizes that managing NPLs is not just a technical or operational task but a central strategy for ensuring banks remain profitable, stable, and resilient over the long term.